Omega-3 attenuates the severity of medication-related osteonecrosis of the jaws in rats treated with zoledronate - Juliano Milanezi de Almeida; Halef Diego Turini; Henrique Rinaldi Matheus; Otávio Augusto Pacheco Vitória; Bianca Rafaeli Piovezan; Ruan Henrique Barra Dalmonica; Elisa Mara de Abreu Furquim; Edilson Ervolino (PLoS ONE, 2025)
This study aimed to evaluate the ability of ω-3 to modulate the tissue response in rats with MRONJ, focusing on histopathological and immunohistochemical parameters. Forty Wistar rats were subjected to bilateral ovariectomy and, three months later, the medication regimen with ZOL (100μg/kg; groups ZOL and ZOL-ω3) of vehicle (VEH and VEH-ω3) was initiated. Following 3 weeks of ZOL or VEH, experimental periodontitis was induced around the mandibular left first molars of all animals. Then, 14 days later (one day before tooth extraction), daily dietary supplementation with ω-3 was given to animals belonging to groups VEH-ω3 or ZOL-ω3. Euthanasia was performed 21 days after tooth extraction. Histologic, histometric (newly-formed bone tissue [NFBT] and non-vital bone tissue [NVBT]), and immunohistochemical (TNF-α, α-SMA, ALP, IL-1β, VEGF, OCN, and TRAP) analyses were performed. Dietary supplementation with ω-3 reduced the amount of NVBT and controlled the intensity and extension of the inflammatory infiltrate in ZOL-ω3, as compared with ZOL. Osteoclast and osteoblast activity were not statistically different between groups ZOL and ZOL-ω3. The structure of the epithelium and the underlining connective tissue were improved by the supplementation with ω-3 in animals under ZOL therapy. Oral supplementation with omega-3 controlled the inflammation and reduced the amount of non-vital bone at the tooth extraction site of ovariectomized rats treated with ZOL and attenuating the severity of MRONJ.